Comparisons of clustered regularly interspaced short palindromic repeats and viromes in human saliva reveal bacterial adaptations to salivary viruses - Pride, David T.; Salzman, Julia; Relman, David A. (Environmental microbiology, 2012)
Summary Explorations of human microbiota have provided substantial insight into microbial community composition; however, little is known about interactions between various microbial components in human ecosystems. In response to the powerful impact of viral predation, bacteria have acquired potent defences, including an adaptive immune response based on the clustered regularly interspaced short palindromic repeats (CRISPRs)/Cas system. To improve our understanding of the interactions between bacteria and their viruses in humans, we analysed 13 977 streptococcal CRISPR sequences and compared them with 2 588 172 virome reads in the saliva of four human subjects over 17 months. We found a diverse array of viruses and CRISPR spacers, many of which were specific to each subject and time point. There were numerous viral sequences matching CRISPR spacers; these matches were highly specific for salivary viruses. We determined that spacers and viruses coexist at the same time, which suggests that streptococcal CRISPR/Cas systems are under constant pressure from salivary viruses. CRISPRs in some subjects were just as likely to match viral sequences from other subjects as they were to match viruses from the same subject. Because interactions between bacteria and viruses help to determine the structure of bacterial communities, CRISPR‐virus analyses are likely to provide insight into the forces shaping the human microbiome.